A Dose- rather than Delivery Profile–Dependent Mechanism Regulates the "Muscle-Full" Effect in Response to Oral Essential Amino Acid Intake in Young Men. Issue 2 (10th December 2014) - Mitchell, William Kyle; Phillips, Beth E; Williams, John P; Rankin, Debbie; Lund, Jonathan N; Smith, Kenneth; Atherton, Philip J
Abstract: Background: The anabolic response of skeletal muscle to essential amino acids (EAAs) is dose dependent, maximal at modest doses, and short lived, even with continued EAA availability, a phenomenon termed "muscle-full." However, the effect of EAA ingestion profile on muscle metabolism remains undefined. Objective: We determined the effect of Bolus vs. Spread EAA feeding in young men and hypothesized that muscle-full is regulated by a dose-, not delivery profile–, dependent mechanism. Methods: We provided 16 young healthy men with 15 g mixed-EAA, either as a single dose ("Bolus"; n = 8) or in 4 fractions at 45-min intervals ("Spread"; n = 8). Plasma insulin and EAA concentrations were assayed by ELISA and ion-exchange chromatography, respectively. Limb blood flow by was determined by Doppler ultrasound, muscle microvascular flow by Sonovue (Bracco) contrast-enhanced ultrasound, and phosphorylation of mammalian target of rapamycin complex 1 substrates by immunoblotting. Intermittent muscle biopsies were taken to quantify myofibrillar-bound 13 C6 -phenylalanine to determine muscle protein synthesis (MPS). Results: Bolus feeding achieved rapid insulinemia (13.6 μIU · mL −1, 25 min after commencement of feeding), aminoacidemia (∼2500 μM at 45 min), and capillary recruitment (+45% at 45 min), whereas Spread feeding achieved attenuated insulin responses, gradual low-amplitude aminoacidemia (peak: ∼1500 μM at 135 min), and no detectable capillary recruitment (all P < 0.01 vs. Bolus). Despite these differences, identical anabolic responses were observed; fasting fractional synthetic rates of 0.054% · h −1 (Bolus) and 0.066% · h −1 (Spread) increased to 0.095% and 0.104% · h −1 (no difference in increment or final values between regimens). With both Spread and Bolus feeding strategies, a latency of at least 90 min was observed before an upswing in MPS was evident. Similarly with both feeding strategies, MPS returned to fasting rates by 180 min despite elevated circulating EAAs. Conclusion: These data do not support EAA delivery profile as an important determinant of anabolism in young men at rest, nor rapid aminoacidemia/leucinemia as being a key factor in maximizing MPS. This trial was registered at clinicaltrials.gov as NCT01735539.